Small body size phenotypes among Middle and Later Stone Age Southern Africans. Issue 152 (March 2021) - Cameron, Michelle E.; Pfeiffer, Susan; Stock, Jay
Abstract: Modern humans originated between 300 and 200 ka in structured populations throughout Africa, characterized by regional interaction and diversity. Acknowledgment of this complex Pleistocene population structure raises new questions about the emergence of phenotypic diversity. Holocene Southern African Later Stone Age (LSA) skeletons and descendant Khoe-San peoples have small adult body sizes that may reflect long-term adaptation to the Cape environment. Pleistocene Southern African adult body sizes are not well characterized, but some postcranial elements are available. The most numerous Pleistocene postcranial skeletal remains come from Klasies River Mouth on the Southern Cape coast of South Africa. We compare the morphology of these skeletal elements with globally sampled Holocene groups encompassing diverse adult body sizes and shapes ( n  = 287) to investigate whether there is evidence for phenotypic patterning. The adult Klasies River Mouth bones include most of a lumbar vertebra, and portions of a left clavicle, left proximal radius, right proximal ulna, and left first metatarsal. Linear dimensions, shape characteristics, and cross-sectional geometric properties of the Klasies River Mouth elements were compared using univariate and multivariate methods. Between-group principal component analyses group Klasies River Mouth elements, except the proximal ulna, with LSA Southern Africans. The similarity is driven by size. Klasies River Mouth metatarsal cross-sectional geometric properties indicate similar torsional and compressive strength to those from LSA Southern Africans. Phenotypic expressions of small-bodied adult morphology in Marine Isotope Stages 5 and 1 suggest this phenotype may represent local convergent adaptation to life in the Cape.